Evaluasi Pembuatan Kartu Kredit di Bank Mandiri Kantor Wilayah 2 Kota Palembang - Ibrahim; Trecy Austin (Jurnal EMT KITA, 2023)
Evaluation of making credit cards at Bank Mandiri Regional Office 2 Palembang. The design of this study used a research method that the author did use a qualitative approach with a descriptive tier. Data or information was collected through interviews with informants to customers.  This study uses data types that include: type of qualitative data obtained through interviews with informants besides that this researcher also makes references to books, laws, or searches. Data collection techniques used in this study include asking questions to informants, observing what is happening in the field, and taking photos of what is happening in the field. In this research, The current data analysis technique is analysis by collecting, condensing, grouping, and summarizing. based on the results of our investigation of the Evaluation of Credit Card Making at Bank Mandiri Regional Office 2 Palembang using evaluation theory according to Stufflebeam (Wirawan 2016:201), namely as follows: 1) Context consists of Objectives, Targets, and applicable rules, 2) Input consists of Human Resources, Funds, and budgets as well as Infrastructure and Facilities, 3) The process consists of The process of making a bank independent credit card 4). The product consists of Credit card benefits for users.